Gamification Analysis in Ui And Ux for Parking Spot Apps - Emmanuel Himawan Saptaputra; Arsa Widitiarsa Utoyo; Nia Karlna (Journal of Games, Game Art, and Gamification, 2020)
Advances in personal computing and information technology have been updated and published online or via mobile devices. Consequently, we must consider interaction as a fundamental complement of representation in cartography and visualization. The user interface (UI) / UX (user experience) describes a series of concepts, guidelines and workflows to critically reflect on the design and use of an interactive, map- based or other product. This entry presents the basic concepts of UI / UX design that is important for cartography and visualization, focusing on issues related to visual design. First, a fundamental distinction is made between the use of an interface as a tool and the broader experience of an interaction, a distinction that separates UI design and UX design. The phases of the Norman interaction framework are not a different form of interaction structure. Finally, three dimensions of the user interface design are described: the fundamental interaction operators that form the basic blocks of the interfaces, the interface styles that these primitive operators implement and the recommendations for the visual design of an interface.